Social science : an introduction to the study of society - Hunt, Elgin F.; Colander, David C. (Boston : Peason/Allyn and Bacon, 2008)
This classic text provides a revised and updated survey of the social sciences, written in an unbiased manner with a multidisciplinary, common sense approach. The Thirteenth Edition highlights the dramatic political and economic changes that have swept the world in recent years, providing students and instructors with a starting point for lively classroom discussions and debate.
Variations of Family Patterns and the Functions of the Family -- The Family in the United States Today -- The Family in Transition -- 9 Religion -- The Nature of Religion -- The Great Religions of Today -- The Role of Religion in Society -- The Future of Religion -- 10 Education -- Schools as Agencies of Social Control -- The Development of U.S -- Education -- Examining the School System -- Interaction of Economics, Politics, and Social Institutions -- 11 Social and Economic Stratification -- Types of Social Stratification -- Social Mobility -- Economic and Social Inequality -- Increasing Social and Economic Inequality -- 12 Stratification, Minorities and Discrimination Race and Ethnicity -- Minorities -- Conclusion -- 13 The Functions and Forms of Government -- The Primary Functions of Government -- Debates about the Nature of Government -- Forms of Government -- Governments Are Far from Simple -- 14 Democratic Government in the United States -- Historical Development of U.S. Government -- The Structure of U.S. Government -- The Political Process -- Evaluation of the Democratic Political Process -- 15 Governments of the World -- French Government -- Nigerian Government -- Japanese Government -- Russian Government -- Saudi Arabian Government -- Some Lessons about Governments -- Future Changes in Governments -- 16 The Organization of Economic Activities -- The Nature of an Economy -- The Evolution of Economic Systems -- Market Economies -- Globalization and the Changing Nature of the U.S. Economy -- The Socialist Economic System -- The Continuing Evolution of Economies -- 17 Government and the Economy -- Government's Direct Role in the Economy -- Government's Indirect Role in the Economy -- Conclusion -- 18 International Political Relations -- The State in International Relation
Includes bibliographical references and index.
1
Keywords: Social sciences